Analisis Keterampilan Ecoliteracy Siswa SDN Cipanagon Melalui Kegiatan Peduli Lingkungan - F Khaerun Nisa; Hatma Heris Mahendra; Febri Fajar Pratama (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
As an effort to contribute to development in order to support sustainable development, it is necessary to have a good understanding of human resources and natural resources. One of them is by studying the relationship between humans and the environment, namely through ecoliteracy activities (literacy that studies humans and the environment) in schools which aim to equip students, so that students can have a good understanding of the environment. This study aims to describe ecoliteracy skills through environmental care activities at Cipanagon Elementary School, find out the inhibiting factors in the process of implementing ecoliteracy in schools, find out alternative solutions that teachers can do in implementing ecoliteracy in schools. This study uses a qualitative approach with descriptive analysis method. Data collection techniques used are through observation techniques, interviews and documentation. Based on the results of the study, it was stated that the ecoliteracy skills of Cipanagon Elementary School students through environmental care activities, had a percentage of 65% included in the good category so that these ecoliteracy skills were well applied at school. This cannot be separated from the teachers' strategies in shaping student character, and supporting the implementation of these ecoliteracy skills.